125I Brachytherapy in Locally Advanced Nonsmall Cell Lung Cancer After Progression of Concurrent Radiochemotherapy. Issue 49 (December 2015) - Xiang, Zhanwang; Li, Guohong; Liu, Zhenyin; Huang, Jinhua; Zhong, Zhihui; Sun, Lin; Li, Chuanxing; Zhang, Funjun
Abstract : Abstract: To investigate the safety and effectiveness of computed tomography (CT)-guided 125 I seed implantation for locally advanced nonsmall cell lung cancer (NSCLC) after progression of concurrent radiochemotherapy (CCRT). We reviewed 78 locally advanced NSCLC patients who had each one cycle of first-line CCRT but had progressive disease identified from January 2006 to February 2015 at our institution. A total of 37 patients with 44 lesions received CT-guided percutaneous 125 I seed implantation and second-line chemotherapy (group A), while 41 with 41 lesions received second-line chemotherapy (group B). Patients in group A and B received a total of 37 and 41 first cycle of CCRT treatment. The median follow-up was 19 (range 3–36) months. After the second treatment, the total response rate (RR) in tumor response accounted for 63.6% in group A, which was significantly higher than that of group B (41.5%) ( P  = 0.033). The median progression-free survival time (PFST) was 8.00 ± 1.09 months and 5.00 ± 0.64 months in groups A and B ( P  = 0.011). The 1-, 2-, and 3-year overall survival (OS) rates for group A were 56.8%, 16.2%, and 2.7%, respectively. For group B, OS rates were 36.6%, 9.8%, and 2.4%, respectively. The median OS time was 14.00 ± 1.82 months and 10.00 ± 1.37 months for groups A and B, respectively ( P  = 0.059). Similar toxicity reactions were found in both groups. Tumor-related clinical symptoms were significantly reduced and the patients' quality of life was obviously improved. CT-guided 125 I seed implantation proved to be potentially beneficial in treating localized advanced NSCLC; it achieved good local control rates and relieved clinical symptoms without increasing side effects.